Seismic Risk Analysis of the Serpong Nuclear Complex and the RSG-GAS Reactor Using Microseismic Methods - Satriyo, A.; Suryanto, W.; Anggono, T.; Subekti, M.; Sucipta, S; Jatnika, J.; Swastikarani, R.; Sugianto, N. (National Research and Innovation Agency, 2025)
The G.A. Siwabessy research reactor (RSG-GAS), located in the Serpong Nuclear Complex (SNC), is a critical component of Indonesia's nuclear research infrastructure. This study aims to assess the seismic safety of the RSG-GAS reactor and its surrounding complex using microseismic methods, specifically the Horizontal-to-Vertical Spectral Ratio (HVSR) and Floor Spectral Ratio (FSR) techniques. HVSR measurements conducted across the B. J. Habibie Science and Technology Area (KST) revealed an average natural frequency (f₀) of 3.49 Hz (range: 2.84-4.43 Hz), amplification factors (A₀) averaging 2.84 (range: 2.11-4.88), and seismic susceptibility indices (Kg) averaging 2.72 (range: 1.34-4.39). The HK9 site, positioned 124 meters from the reactor, exhibited lower-than-average values, indicating reduced seismic vulnerability in the immediate reactor vicinity. FSR analysis was conducted to evaluate key structural parameters, including the Resonance Index (IR), inter-level deviation (γⱼ), peak ground acceleration (αbⱼ), and Building Vulnerability Index (Ktgⱼ). Most IR values fell within the medium-risk range (20.07 %-22.63 %), while one measurement point recorded 3.98 %, indicating high resonance risk. Inter-level deviations remained within acceptable safety thresholds; however, peak ground acceleration values exceeded critical limits at several levels, most notably at FU8 where 272.63 gal was recorded at -6.5 m elevation-significantly surpassing established safety standards. Several Building Vulnerability Index values also exceeded recommended safety limits. The findings demonstrate that while the RSG-GAS facility generally exhibits low-to-moderate seismic amplification and structural vulnerability, targeted structural reinforcements are essential at critical locations, particularly at the FU8 level. This study provides a comprehensive framework for enhancing seismic resilience of nuclear facilities in seismically active regions and contributes to the long-term safety assessment protocols for Indonesia's nuclear infrastructure.